The Distribution, Damage and Control of the Rootknot Nematode, Meloidogyne Incognita (Kofoid and White) Chitwood on Tobacco in Malaysia - Sidam, Abd. Karim (1988)
The present study attempts to map the distribution of Meloidogyne species in Kelantan, establish the pathogenecity of M. incognita on tobacco and to find out suitable control methods of the nematode on tobacco. Nematode survey showed that ten plant-parasitic species were associated with tobacco in Kelantan. The nematode species were Meloidogyne incognita, M.javanica, He licotylenchus crenacauda, Ro tylenchulus reniformis, Macroposthoni ornata, Pr atylenchus zeae, Xiphinema citri, X. radicicola, Ty lenchorhyn chus annulatus, and Hirschmanniella.